Ismétlés a megismétlődés ellen: Reenactment, holokauszt, dilemmák - Turai, Hedvig (Studia Litteraria, 2024)
The first Holocaust reenactments happened right after the liberation of the camps when, as a mode of testimony and authentication of their experience, survivors themselves “reenacted” for their liberators what happened to them. When artistic reenactments entered the Holocaust discourse, it was in a different historical situation. By the 2000s, when artistic reenactment was at its peak, (1) the way to use the tools of contemporary art in connection with the Holocaust had already been paved, so that contemporary artistic strategies could be used efficiently to evoke memory and memorialization. (2) There were new disciplinary currents within history, with post-structuralism having raised complex questions in connection with the Holocaust. History’s affective turn focused on historical actors whose experiences had earlier remained unknown, invisible or had not been considered significant. (3) Important and urgent questions about the representation of the Holocaust had been widely debated in conferences, books, and were still ongoing. Reenactment can be an efficient way to evoke the Holocaust, its unknown, erased, destroyed evidence, especially after the age of direct witness and testimony had lapsed. The paper discusses a few artistic attempts to approach the mediation of the Holocaust, and the specific difficulties these reenactments face, as well as the reason why artistic-historical imagination cannot always find favourable reception.